Effect Of Pomegranate (Punica granatum L.) Fraction In Reducing Total Blood Cholesterol Levels and Triglyceride in Mice (Mus muscullus L.) - Nurlaily Agustini; Arum Setiawan; Salni Salni (Research Centre of Inorganic Materials and Complexs, 2020)
Pomegranate (Punica granatum L.) will be examined by looking at the ability between pomegranate extracts or fractions, which are more effective in lowering total blood cholesterol and triglyceride levels in mice. This study aims to determine the active pomegranate fraction that can reduce the total cholesterol levels and triglyceride in mice. The research method used was an experimental method with a Completely Randomized Design (CRD) which was divided into 6 treatment groups, and test animals divided into 6 treatment groups namely negative control given aquades, positive control fed a high-fat diet, given simvastatin, given 25 mg/grBB of pomegranate methanol fraction, given 50 mg/grBB of pomegranate methanol fraction, given 100 mg/grBB of pomegranate methanol fraction, each treatment group will be divided into 4 male mice.Based on the results of this study that the active fraction that has an effect in reducing blood cholesterol levels and mice triglycerides is the treatment given 100mg/grBB of pomegranate water methanol fraction.